Vegetative anatomy of three potted Chrysanthemum varieties under various paclobutrazol concentrations - Intani Quarta Lailaty; Laurentius Hartanto Nugroho (Society for Indonesian Biodiversity, 2021)
Abstract. Lailaty IQ, Nugroho LH. 2021. Vegetative anatomy of three potted Chrysanthemum varieties under various paclobutrazol concentrations. Biodiversitas 22: 563-570. Chrysanthemum is one ornamental plant with high potential to be developed commercially. It has many varieties such as colors, types, and shapes of flowers. Paclobutrazol (PBZ) is one of plant growth regulators used to suppress plant growth. The PBZ action mechanism is to inhibit gibberellin synthesis. The application of PBZ with a certain concentration on Chrysanthemum plants has the potential to form potted Chrysanthemum. The aim of this study was to analyze the anatomical variation of potted mums varieties, i.e. Jaguar Red, Snow White and Fiji White, and also the effect of PBZ with various concentrations on the anatomy of the stems and leaves of three Chrysanthemum varieties. The research was conducted by applying PBZ concentrations of 0, 50, 100, 150 ppm to the three Chrysanthemum varieties and grown for 8 weeks to form potted Mums. Then, the anatomy of stems and leaves was studied using the paraffin and freehand section methods. Data analysis was performed using ANOVA and DMRT (Duncan Multiple Range Test) for anatomical characters in stems and leaves of three Chrysanthemum varieties. The results showed that the length of the epidermal cells of Fiji white variety was longer than those of Snow White and Jaguar Red. Meanwhile, Jaguar Red produced greater stem thickness, stomata, and leaf thickness than those of the other two varieties. PBZ could increase the size of the anatomical parameters of Chrysanthemum stems and leaves for all varieties. The PBZ concentration of 150 ppm increased leaf thickness and stem diameter, as well as tracheal diameter. The PBZ concentration of 100 ppm increased the size of the guard cells, palisade and spongy tissue, also peripheral tissues. Meanwhile, the PBZ concentration of 50 ppm had an effect on the increase in the number of stomata and pith diameter. The optimum PBZ concentration to form potted Chrysanthemum was 150 ppm.